An anatomy of murder - Omer, Spahic (www.islamicity.org, 2019)
The dignity and honor of man are undisputed. That is because Almighty Allah, the Creator, explicitly affirms that He has honored the children of Adam, and has conferred on them special favors, over a great part of creation (al-Isra’, 70). Everything especially on earth has been created in order to serve man as Allah’s vicegerent, and to facilitate the execution of his noble earthly mission and purpose. Similarly, everything that man himself creates, as part of his continuous cultural and civilizational functioning, is to resonate the same meaning and aid the same objective. In a nutshell, man stands at the center of creation with all other dimensions and aspects of life existing primarily to validate, constantly uplift and sustain the nobility and excellence of man. The foremost criteria for evaluating a civilization revolve around what type of human beings it produces, and to what extent it is disposed to the preservation of human life, dignity and the inherent distinction of man. It is on account of this that the Qur’an warns that whoever killed an innocent soul or a human being, it would be in the sight of Allah as if he killed all mankind. But whoever saved one, it would be as if he saved all mankind (al-Ma’idah, 32). Moreover, about killing intentionally an innocent believer, the Qur’an categorically states that “his recompense is Hell, wherein he will abide eternally, and Allah has become angry with him and has cursed him and has prepared for him a great punishment” (al-Nisa’, 93). Indeed, there is nothing that can sanction and justify taking an innocent human life. No clause in a legal framework can accommodate such an inhuman act, nor can a sound mind have any capacity to dwell on such a matter, let alone agree to it. Murder is heartless, merciless, barbaric and most disgraceful. It is an anomalous act, incompatible with any rationality, morality, and the intended cultural plus civilizational wellbeing of people. That is why when a murder occurs, the best form of justice is that a murderer publically pay with his own life as a form of general deterrence, so as to prevent others who may have identical intentions from committing identical crimes in the future. And that means protecting and cherishing the true meaning of life: “And there is for you in legal retribution or qisas (saving of) life, O you (people) of understanding, that you may become righteous (restrain yourselves)” (al-Baqarah, 179). Indeed, being firm and unyielding towards murder and murderers means respecting life and those who want to live it responsibly and nobly. All human initiatives and rules must reflect that and be totally in support of the truth, justice, righteousness and peace.